Phenotypic and Genetic Variation of an Interspecific Centaurium Hybrid (Gentianaceae) and Its Parental Species - Banjanac, Tijana (Plants (Basel), 2019)
Interspecific hybridization is one of the major actuators of evolutionary changes in plants. As the result of allopolyploid hybridization, offspring may gain different ploidy levels in comparison to parental species, which can provide them instant reproductive isolation. Two tetraploid sister species, Centaurium erythraea and C. littorale, readily cross-fertilize, resulting in hybrids of various ploidy. In northern Serbia, two stable populations of a hexaploid taxon C. pannonicum have been documented. It has been proposed previously that this taxon emerged after an interspecific hybridization event between two tetraploid sister-species: C. erythraea and C. littorale subsp. compressum. The existing populations of the hybridogenic taxon, as well as neighboring populations of the two parental taxa were here characterized by both morphometrics and molecular markers (EST-SSR and trnL-F). Three leaf and two flower characteristics were found to be informative in delimitation of the parental taxa and in their discernment from hybrid individuals, the latter having intermediate values. Eight microsatellite markers were found to have good ability to distinguish studied taxa, placing C. pannonicum in closer relationship with C. erythraea. Conversely, trnL-F plastid marker nominated C. littorale subsp. compressum to be the donor of the C. pannonicum plastid DNA. Reproductive isolation of the hexaploid hybrid individuals from the parental species should be examined as the next logical step in describing the new species.